2018
DOI: 10.1038/s41598-018-30522-6
|View full text |Cite
|
Sign up to set email alerts
|

Gingerol suppresses sepsis-induced acute kidney injury by modulating methylsulfonylmethane and dimethylamine production

Abstract: Acute kidney injury (AKI) and metabolic dysfunction are critical complications in sepsis syndrome; however, their pathophysiological mechanisms remain poorly understood. Therefore, we evaluated whether the pharmacological properties of 6-gingerol (6G) and 10-gingerol (10G) could modulate AKI and metabolic disruption in a rat model of sepsis (faecal peritonitis). Animals from the sham and AKI groups were intraperitoneally injected with 6G or 10G (25 mg/kg). Septic AKI decreased creatinine clearance and renal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…The COVID-19 pandemic has also caused a high demand for ginger globally ( Ayipey, 2020 ), which is reflected in our study’s findings as more than 80% of participants reported increasing their ginger intake during this pandemic. A considerable body of evidence supports ginger’s therapeutic values in pulmonary and inflammatory conditions such as pneumonia, pulmonary fibrosis, and sepsis, which are all pertinent to COVID-19, though a direct link has not been established yet ( Panyod et al, 2020 , Rodrigues et al, 2018 , Shariatpanahi et al, 2010 , Thota et al, 2020 ). The evidence also supports a therapeutic value for other natural products and foods such as turmeric, curcumin, cinnamon, lemon, basil, and pepper, which were also being increasingly consumed by our study’s population ( Thota et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has also caused a high demand for ginger globally ( Ayipey, 2020 ), which is reflected in our study’s findings as more than 80% of participants reported increasing their ginger intake during this pandemic. A considerable body of evidence supports ginger’s therapeutic values in pulmonary and inflammatory conditions such as pneumonia, pulmonary fibrosis, and sepsis, which are all pertinent to COVID-19, though a direct link has not been established yet ( Panyod et al, 2020 , Rodrigues et al, 2018 , Shariatpanahi et al, 2010 , Thota et al, 2020 ). The evidence also supports a therapeutic value for other natural products and foods such as turmeric, curcumin, cinnamon, lemon, basil, and pepper, which were also being increasingly consumed by our study’s population ( Thota et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress was assessed by measuring the oxidative stress biomarkers, such as MDA (malondialdehyde), NOx (the indirect assessment of NO synthesis), total oxidative stress (TOS), and plasma antioxidant status was assessed by measuring the thiol, catalase and total antioxidant capacity (TAC) plasma level, as described previously [ 55 , 56 ].The plasma parameters of oxidative stress/antioxidant capacity were assessed using a spectrophotometer (Jasco International Co., Ltd., Tokyo, Japan). MDA assessment was made by using thiobarbituric acid reaction, reported as a standard method [ 57 , 58 , 59 ]. Briefly, the serum sample was mixed with trichloracetic acid and vigorously vortexed, then thiobarbituric acid was added.…”
Section: Methodsmentioning
confidence: 99%
“…Both compounds have also reduced the levels of oxidative stress markers, MDA and nitrite, as well as increased the levels of antioxidants, GSH and SOD. In addition, they also reduced levels of inflammatory markers such as tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, and kidney injury marker, KIM‐1 (Rodrigues et al, 2018).…”
Section: Therapeutic Properties Of Natural Productsmentioning
confidence: 99%